Cheating and resistance to cheating in natural populations of the bacterium Pseudomonas fluorescens - Bruce, J; Cooper, G; Chabas, H; West, S; Griffin, A (Wiley, 2017)
Bacteria perform cooperative behaviors that are exploitable by noncooperative cheats, and cheats frequently arise and coexist with cooperators in laboratory microcosms. However, evidence of competitive dynamics between cooperators and cheats in nature remains limited. Using the production of pyoverdine, an iron-scavenging molecule, and natural soil populations of Pseudomonas fluorescens, we found that (1) nonproducers are present in the population; (2) they co-occur (<1cm3 ) with pyoverdine producers; (3) they retain functional pyoverdine receptors; and (4) they can use the pyoverdine of on average 52% of producers. This suggests nonproducers can potentially act as social cheats in soil: utilizing the pyoverdine of others while producing little or none themselves. However, we found considerable variation in the extent to which nonproducers can exploit producers, as some isolates appear to produce exclusive forms of pyoverdine or kill nonproducers with toxins. We examined the consequences of this variation using theoretical modeling. We found variance in exploitability leads to some cheats gaining increased fitness benefits and others decreased benefits. However, the absolute gain in fitness from high exploitation is lower than the drop in fitness from low exploitation, decreasing the mean fitness of cheats and subsequently lowering the proportion of cheats maintained in the population. Our results suggest that although cooperator-cheat dynamics can occur in soil, a range of mechanisms can prevent nonproducers from exploiting producers.